Thermodynamic analysis and preferential solvation of sulfamethazine in acetonitrile+ water cosolvent mixtures (2019)
This paper presents the solubility of sulfamethazine (SMT) in the acetonitrile (MeCN) + water (W) cosolvent system at nine temperatures. From the solubility experimental data, the thermodynamic functions of solution, mixing, and transfers are calculated and analyzed using the Perlovich graphical method. On the other hand, an enthalpy−entropy compensation analysis is performed and the preferential solvation parameters are calculated using the Kirkwood-Buff (IKBI) inverse integral method. The result of the performed calculations indicates that the SMT solution process is endothermic with entropic favor, where the addition of MeCN has a positive cosolvent effect between pure water and the mixture with w1 = 0.90. As for the preferential solvation, the SMT molecule is preferentially surrounded by water in water- and MeCN-rich mixtures, and in intermediate mixtures, the SMT molecule tends to be surrounded by MeCN.